THE EFFECTIVENESS OF A CORE MUSCLES STABILITY PROGRAM IN REDUCING THE POSTURAL SWAY OF ADOLESCENT ARCHERS: A PANACEA FOR A BETTER ARCHERY PERFORMANCE (International Journal of Physiotherapy, 2017)
Background: Expert athletes in archery can rapidly achieve postural stability compared to beginners and novice athletes. This study investigated the effectiveness of a core stability training program in reducing the postural sway among adolescent archers.Methods: Participants (n=12) of this study were aged between 13-18 years; were divided into two groups (i.e., experimental and control). The experimental group underwent a supplementary eight-week core stability training program apart from their regular training program. Data were collected at three-time points; pre, after four weeks and post-training. Postural sway was measured in the anteroposterior plane and medio-lateral plane – center of pressure (CoP).Results: Mixed factorial ANOVA yielded significant interactions over time in the performance of the push up; plank; archery performance and postural sway. Postural sway between the experimental and control group was significantly different on both planes at T2; (CoP range x - F(1,10) = 7.952, p